The Syrian and Lebanese Migrants in Colonial French West Africa, 1880s-1930s - (:unkn) unknown (My University, 2017)
Thanks to the study of the French West Africa’s Gouvernement-général archives and through a social history view, this article explores chain migration between Mount Lebanon villages and French West Africa’s settlements, mostly Guinea and Senegal, from their establishment in the 1880s to 1939, before the implementation of French imperialist policy, through a turning point both in the Middle East and in West Africa. First, it aims to illuminate the transnational migration of « Syro-Libanais », known as such in French colonial archives, identifying various actors and their respective roles in migration framing abroad. It seeks to underscore the importance of transnational social networks into which migrants were integrated by merit of possessing specific economic and social capital. Finally, this article focuses on how French colonial power in Africa used various ideologies to conceptualize and control foreign migration in Africa. Specifically examined are the liberal policy that was open to all potential actors and contributed to the settlement's « mise en valeur » (development) before the turning point of Great Depression in the early 1930s and the autarkic policy that followed.
Keywords: African Research